Back Cover: Solid‐State Structural Transformations and Photoreactivity of 1D‐Ladder Coordination Polymers of PbII (Chem. Eur. J. 12/2013). Issue 12 (8th March 2013) - Kole, Goutam Kumar; Peedikakkal, Abdul Malik Puthan; Toh, Belinda Mei Fang; Vittal, Jagadese J.
<x xml:space="preserve">Abstract</x> One‐dimensional coordination polymers (CPs) containing ladder structures are ideal to conduct [2+2] cycloaddition reactions. While attempting to align the bis(4′‐pyridyl)ethylene ligand pairs using PbII and three different benzoate anions, linear photostable CPs were obtained with a hydrogen‐bonded water chain in the lattice as a kinetic product. On removal of the lattice water, the polymers rearrange to a ladder structure. One of the three ladder structures synthesized undergoes a single‐crystal‐to‐single‐crystal photochemical reaction to give the cyclobutane‐containing coordination polymer as described in the Full Paper by J. J. Vittal on page 3962 ff. The backgournd photo is the 2nd Howrah bridge, Kolkata (India).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>